Desenvolvimento de nanoestruturas de TiO2 com superfície modificada pela presença de espécies de Fe e a avaliação da sua performance fotocatalítica - Falsetti, Paulo Henrique Eleuterio (2022)
The development of society has increasingly demanded technological evolution in order to supply its needs, resulting in environmental costs that can lead to severe damage. Among these impacts, the pollution of springs and atmospheric air through the emission of different residual chemical compounds from human activities stands out. Therefore, heterogeneous photocatalysis presents itself as an effective method for the remediation of both problems, which justifies the current need to develop more effective photocatalysts. Thus, the present work aimed to develop a more effective photocatalyst, such as TiO2 nanostructures with a surface modified by the presence of Fe species. The photocatalytic potential was evaluated against the degradation of two organic dyes, methylene blue and rhodamine B, as well as for the photoreduction of CO2, which is considered one of the most worrying gaseous pollutants. The TiO2 nanostructures were obtained through the hydrothermal method from the degradation of ammonium peroxo titanate (PTA) at different pH values of the reaction medium (equal to 6, 8 and 10). Subsequently, the as-obtained and commercial samples of TiO2, used as a reference, were decorated with Fe in different proportions (0.2, 0.8 and 1.6 % by mass of Fe) in relation to the mass of TiO2, followed by heat treatment at 400 ºC for 4 hours. X-ray diffraction measurements revealed the same TiO2 anatase crystalline phase for all samples, while UV-Vis diffuse reflectance spectroscopy (DRS) measurements showed that the presence of Fe in the samples leads to a change in their optical properties, with an increase in the absorption spectrum in the visible region and a change in the band gap values compared to pure TiO2 nanostructures. Electron microscopy analyses evidenced the formation of nanoparticles with different morphologies due to the applied synthetic conditions and compared to commercial sample, where the samples synthesized at pH equal to 8 showed anisotropic morphologies with a tendency to grow in specific crystalline planes. EDX analyses confirmed the presence of Fe on the surface of TiO2 nanostructures in a well-distributed way in the particles. Raman spectroscopy measurements indicated that the increased presence of Fe results in surface defects in the structure, which can be attributed to an inter-diffusion process of Fe in the TiO2 nanostructures. X-ray photoelectron spectroscopy (XPS) analyses confirmed the presence of different Fe species on the surface of samples as well as changes in the chemical environment of Ti related to the presence of these species. The photocatalytic performance study of the samples revealed that their photocatalytic efficiency in the degradation of dyes is inversely proportional to the amount of Fe, being this result attributed to the superficial alterations caused by the presence of Fe species in the nanostructures. However, the studied samples showed good capacity for photoreduction of CO2 in products with higher added value, such as CH4 and CO, with the sample synthesized at pH 8 and with the highest amount of Fe showing the best photocatalytic potential, evidencing the important role played by the morphology of the material obtained and the amount of Fe in its photocatalytic performance. Therefore, the results demonstrate that the morphology and Fe amount can define the best applicability of the sample to either the deconstruction (dye degradation) or construction of molecules (CO2 photoreduction).